(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article examines the development of self-directed learning through a strategy-based approach in foreign language education. Self-directed learning is considered a crucial competence that enables learners to take responsibility for planning, monitoring, and evaluating their own learning process. The study aims to explore how the systematic use of learning strategies can enhance learners’ autonomy and motivation. A strategy-based approach is analyzed as an instructional framework that explicitly teaches cognitive, metacognitive, and socio-affective strategies to support independent learning.